The avant-garde artistic approaches of Russian women writers of the Silver age - Terno-Jeleńska, Weronika (Vilnius University Open Series, 2024)
The article presents the avant-garde, and thus the work of Russian women writers, poets and publicists of the Silver Age, centred on new forms and bold, often provocative plots. The subject of characterisation is the creative attitudes of those authors who, in the period in question, in accordance with the spirit of the epoch, firstly, revealed their individuality to readers and, secondly, touched upon themes ‘forbidden’ up to that time. The author makes an attempt to present the work of those Russian women writers who, in connection with the multifaceted development of literature at the turn of the century, created works in a new style, centered around such issues as: love (in its various guises), gender attitudes and the involvement of women in various conflicts of the surrounding reality. The exploratory analysis of women’s writing of the late nineteenth and early twentieth centuries has shown that the new modern era, characterised by a diversity of schools and creative groupings, contributed to the expansion of the boundaries of the themes of women’s literature.